2014
DOI: 10.1210/en.2013-2043
|View full text |Cite
|
Sign up to set email alerts
|

Predominant Role of GIP in the Development of a Metabolic Syndrome-like Phenotype in Female Wistar Rats Submitted to Forced Catch-up Growth

Abstract: Catch-up growth has been associated with the appearance of metabolic dysfunctions such as obesity and type 2 diabetes in adulthood. Because the entero-insular axis is critical to glucose homeostasis control, we explored the relevance of the incretins glucose-dependent insulinotropic polypeptide (GIP) and glucagon-like peptide-1 (GLP-1) in the development of these pathologies. Offspring of rat dams fed ad libitum (control [C]) or 65% food-restricted during pregnancy and suckling time (undernourished [U]) were w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
12
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 58 publications
4
12
0
Order By: Relevance
“…1c, suggest that (Pro3)GIP is in fact an antagonist of the human GIPR. Our findings coincide with a large body of research demonstrating the antagonistic effects of (Pro3)GIP at the GIPR (Gault et al, 2002; Gault et al, 2003; De Toro-Martin et al, 2014). The summation of these results, as well as previous data demonstrating the efficacy of twincretin at both receptors in vivo (Finan et al, 2013) suggests that twincretin almost certainly induces significant cAMP production via both receptors in neural cells.…”
Section: Discussionsupporting
confidence: 90%
“…1c, suggest that (Pro3)GIP is in fact an antagonist of the human GIPR. Our findings coincide with a large body of research demonstrating the antagonistic effects of (Pro3)GIP at the GIPR (Gault et al, 2002; Gault et al, 2003; De Toro-Martin et al, 2014). The summation of these results, as well as previous data demonstrating the efficacy of twincretin at both receptors in vivo (Finan et al, 2013) suggests that twincretin almost certainly induces significant cAMP production via both receptors in neural cells.…”
Section: Discussionsupporting
confidence: 90%
“…In this study, we showed that impaired nutrient supply during perinatal growth-induced adaptive changes, leading to metabolic disorders, such as obesity, impaired glucose tolerance, insulin resistance, dyslipidemia, and nonalcoholic fatty liver disease when the organism was challenged with increased caloric intake. Our results are consistent with previous studies showing that maternal imbalanced nutrition-induced detrimental consequences on glucose and lipid homeostasis (Claycombe et al 2013;Baik et al 2014;De Toro-Martin et al 2014;Sellayah et al 2014). Therefore, maternal undernutrition results in lower birth weight that is accompanied by the development of chronic metabolic diseases in later life.…”
Section: Discussionsupporting
confidence: 93%
“…Recently, a promising GIP receptor antibody, Gipg013, with a K i of 6.8 nM was reported (Ravn et al ., ). Based on the numerous rodent studies that displayed promising improvements in the diabetic and/or obese state, (Pro3)GIP showed potential to fill the role as a promising antagonist in the context of GIP physiology (Gault et al ., ; Irwin et al ., ; McClean, ; De Toro‐Martin et al ., ). In ob / ob mice, chronic treatment with (Pro3)GIP improved glucose tolerance and insulin sensitivity (Irwin et al ., ), while treatment in mice previously on a high‐fat diet resulted in weight loss, improved insulin sensitivity and glucose tolerance (McClean, ).…”
Section: Discussionmentioning
confidence: 97%